2009
DOI: 10.1152/ajprenal.00156.2009
|View full text |Cite|
|
Sign up to set email alerts
|

Npt2a and Npt2c in mice play distinct and synergistic roles in inorganic phosphate metabolism and skeletal development

Abstract: Hereditary hypophosphatemic rickets with hypercalciuria (HHRH) is a rare autosomal recessively inherited disorder, characterized by hypophosphatemia, short stature, rickets and/or osteomalacia, and secondary absorptive hypercalciuria. HHRH is caused by a defect in the sodium-dependent phosphate transporter (NaPi-IIc/Npt2c/NPT2c), which was thought to have only a minor role in renal phosphate (P(i)) reabsorption in adult mice. In fact, mice that are null for Npt2c (Npt2c(-/-)) show no evidence for renal phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 26 publications
3
113
0
2
Order By: Relevance
“…PiT-2 (SLC20A2) is encoded by a member of the SLC20 family (28). Within the proximal tubule in rats and mice, the abundance of Npt2a gradually decreases along the proximal tubule, whereas Npt2c and PiT-2 are expressed mainly in the first (S1) segment (29). Work from knockout studies in rodents has shown that in mice, Npt2a is responsible for the majority (approximately 70%) of the renal regulation of phosphate transport (29).…”
Section: Renal Regulation Of Phosphate Balancementioning
confidence: 99%
“…PiT-2 (SLC20A2) is encoded by a member of the SLC20 family (28). Within the proximal tubule in rats and mice, the abundance of Npt2a gradually decreases along the proximal tubule, whereas Npt2c and PiT-2 are expressed mainly in the first (S1) segment (29). Work from knockout studies in rodents has shown that in mice, Npt2a is responsible for the majority (approximately 70%) of the renal regulation of phosphate transport (29).…”
Section: Renal Regulation Of Phosphate Balancementioning
confidence: 99%
“…A variety of mutations including compound heterozygous deletion and missense mutations in Npt2c have been identified in other families with HHRH. Pi transport studies in a Xenopus oocyte system revealed that NPT2c gene mutations significantly decreased Na + -dependent Pi transport activity (88). These observations suggest that NPT2c has an important role in renal Pi reabsorption and bone mineralization, and that it may be a key determinant of plasma Pi concentration in humans.…”
Section: Npt2cmentioning
confidence: 84%
“…This autosomal recessive disorder is characterized by hypophosphatemia, renal Pi wasting, increased serum 1,25 dihydroxyvitamin D 3 concentrations, hypercalciuria, rickets, and osteomalacia (83)(84)(85)(86)(87)(88). A genomewide scan combined with homozygosity mapping using DNA from 10 patients with HHRH (83) identified a single nucleotide deletion (c.228delC) in all individuals in the initial cohort affected with HHRH.…”
Section: Npt2cmentioning
confidence: 99%
“…1,2,4 The absence of NaPi-IIa induces massive renal losses of phosphate, leading to hypophosphatemia, rickets, and hypercalciuria. Hypercalciuria is the consequence of elevated vitamin D 3 levels stimulating intestinal calcium hyperabsorption and subsequent renal excretion.…”
mentioning
confidence: 99%
“…7 Deletion of NaPi-IIc (Slc34a3) in mice is fully compensated because no hyperphosphaturia or hypophosphatemia occurs. 4 The role of these transporters in human kidney is much less clear. Missense mutations and large deletions in the NaPi-IIc (SLC34A3) gene in patients with hereditary hypophosphatemic rickets with hypercalciuria indicate that NaPi-IIc is critical for determining serum phosphate levels and urinary phosphate excretion.…”
mentioning
confidence: 99%